2014
DOI: 10.1186/1471-2334-14-236
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal HIV-1 viremia on lymphocyte subsets among HIV-exposed uninfected infants: protective mechanism or immunodeficiency

Abstract: BackgroundReports of increased morbidity and mortality from infectious diseases among HIV Exposed Uninfected (HEU) infants have raised concern about a possible underlying immunodeficiency among them. The objective of this study was to assess the immunological profile of HEU infants born to mothers exhibiting different levels of HIV-1 viremia at the time of delivery.MethodsStudy subjects were enrolled in the Centre maternel et infantile sur le SIDA (CMIS) mother-child cohort between 1997 and 2010 (n =585). Infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…We report significantly higher peripheral frequencies of cells resembling MDSC, in HIV uninfected children born to mothers with HIV infection (HEU), compared to unexposed controls. Increased disease susceptibility of HEU children have been attributed to HIV‐specific T cell responses, primed by maternal HIV antigens, the immaturity or immunosuppressive state of infants’ adaptive immune system or excessive immune activation in the HIV infected mother . Considering the previously reported potent immunosuppressive abilities of MDSCs , our findings could suggest an additional description of the vulnerability of the HEU child's immune system, driven by regulatory innate immune cells.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We report significantly higher peripheral frequencies of cells resembling MDSC, in HIV uninfected children born to mothers with HIV infection (HEU), compared to unexposed controls. Increased disease susceptibility of HEU children have been attributed to HIV‐specific T cell responses, primed by maternal HIV antigens, the immaturity or immunosuppressive state of infants’ adaptive immune system or excessive immune activation in the HIV infected mother . Considering the previously reported potent immunosuppressive abilities of MDSCs , our findings could suggest an additional description of the vulnerability of the HEU child's immune system, driven by regulatory innate immune cells.…”
Section: Discussionmentioning
confidence: 57%
“…Importantly, evidence show that HEU children are at greater risk to acquire and succumb to infectious diseases, when compared with children of uninfected mothers. The mechanisms underlying increased susceptibility and dissemination of TB in HEU children, is not fully understood, but it is suggested that immaturity of infant immune cells , in‐utero exposure to HIV antigens , immune activation of the , may drive these changes .…”
Section: Introductionmentioning
confidence: 99%
“…Offspring born to women with advanced HIV infection and eventually at higher risk of maternal mortality during childhood might be particularly vulnerable. In addition to an adverse social and economic background, compared with healthy mothers, those who are immunodeficient or clinically unwell might be less able to provide appropriate child care, adequate duration of breastfeeding or more likely to carry infectious pathogens harmful to their infants [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…First the virus, including viral proteins, may have a direct proinflammatory effect on placental cells as well as on the developing infant's immune system. Correlations have been described between maternal viral load and the infant's CD4 þ T-cell count [101]. The virus may be recognized as foreign by components of the fetal immune system and induce inflammation, whereas at the same time viral proteins transferred across the placenta could have individual effects.…”
Section: Long-term Effects Of Fetal Exposure To Hiv On Infant Healthmentioning
confidence: 99%